A Gain Programmable Analog Divider Circuit Based on a Data Converter - Asl, S. N.; Tarkhan, M.; Nia, M. S. (Engineering, Technology & Applied Science Research, 2017)
Analog dividers are widely used in analog systems. Analog realization of such circuits suffer from limited dynamic range and non-linearity issues, therefore, extra circuitry should be required to compensate these types of shortcomings. In this paper a gain controllable, analog divider is proposed based on data converters. Our circuit can be implemented both in current and voltage mode by selecting proper architectures. The resolution, power consumption and operation speed can be controlled by proper selecting of components. Another advantage of our circuit is its gain programmability. Moreover, the gain can be adjusted independently based on the relationship between input signals. Our proposed method offers two different gain control abilities, one for situation that the numerator signal is bigger than the denominator, and another gain is applied when the denominator is larger than the numerator. As a result, no extra amplifier is required for signal amplification. Moreover, the input and output signal nature can be chosen arbitrarily in this circuit, i.e. input signal may be a voltage signal while the output signal is current. Simulation results from SPICE confirm the proper operation of the circuit.